Synchronized online simulation at field level for virtual sensing of web tension - Darius Deubert; Stephan Schultze; Andreas Selig; Alexander Verl (Discover Applied Sciences)
Abstract In industrial automation, online simulation should reflect a real mechatronic system as accurate as possible. However, the simulation could drift away from the real manufacturing process due to imprecise modeling or changing system behavior. While in literature, some methods are already used to synchronize digital twins or online simulations of processes to their real counterpart, this article systematically describes the comprehensive field of synchronizing online simulations of manufacturing systems by defining several types of synchronization, explaining their functions, and indicating exemplary realization methods in this context. Subsequently, the concepts are applied to a newly presented use case of online simulation at field level for the demonstration of the proposed concepts. In particular, an exemplary synchronized online simulation is implemented that serves as a virtual sensor for web tension in an imitated web transport system. For this use case, an individual synchronization strategy based on the described methods is presented. The results are validated and discussed based on an experiment, where the behavior of the web transport system is rapidly changing and the synchronized online simulation is adapting accordingly. The findings of this research contribute to the aim of using existing simulation models for online simulation in the operation phase of manufacturing systems.